Effects of slow-release fertilizers of zinc and iron on growth performance in the pisciponic system of Lemon fin barb hybrids Brassica rapa L. var. Chinensis - Mohd Nasir, Maizatiey Farizza (2021)
The challenge of finding an optimal supplementation in a pisciponic system is due to its nutrient input and nutrient uptake as the main element in the system. A good amount of fish without enough nutrients leads to low production of crop plants in a pisciponic system. Other than that, it has been reported that the pisciponic system that relies exclusively on fish waste to provide nutrients for plants have low levels of micronutrients (Ru et al., 2017). Granular fertilization is an interesting strategy for nutrition with micronutrients in the pisciponic system. Among the micronutrients, Zinc (Zn) and Iron (Fe) are the most frequent in the system. A pisciponic system is an integrated farming concept that combines fish and hydroponic plant production in a recirculating water system. However, finding an optimal supplementation in the pisciponic system is challenging due to its nutrient input and nutrient uptake as the main element in the system. Therefore, having a good amount of fish with insufficient nutrients would lead to low production of crop plants in the pisciponic system. Ru et al. (2017) reported that the pisciponic system relies exclusively on fish waste to provide nutrients for plants that contain a low level of micronutrients. Granular fertilization is, hence, suggested as an interesting strategy for nutrition with micronutrients in the pisciponic system, which consist of Zinc (Zn) and Iron (Fe) since these elements are frequently lacking in the system. The present study aims to investigate the effects of supplementation in the pisciponic system on growth performance through granular form application for the plants in the pisciponic system. The study was conducted at the Aquaculture Experimental Station in Puchong, Selangor. The experiment was set up in a greenhouse covered with plastic liner at the bottom. The coated fertilizers were immersed into the beakers containing 500 ml of distilled water. The immersion times were analyzed for each 3, 6 12, 18, 24, 30, 36, 42, 48, 54, 60, 66, and 72 hours. Insoluble solids and water were then filtered using a filter paper and dried in the oven, followed by the drying process to obtain a constant weight before being put in the desiccators. During the release test, the distilled water was taken at every 48-hour interval and the concentration nutrients were determined from the atomic absorption spectrometer. A second experiment was conducted to evaluate the effect of selected micronutrients in the pisciponic system. The coated zinc and iron were placed in each pot with different treatment levels. Seedlings of pak choi were transferred into the pisciponic system 14 days after sowing and harvesting were conducted after 30 days. The weights of release fertilizers, specifically Zn and Fe were significantly decreasing over time. At the lowest concentration, the weights of coated zinc and iron were decreasing as time increased. According to Borges et al. (2012), the amount of fertilizers supplied would affect the amount of SPAD values and the chlorophyll. By referring to the curve results, the Zn fertilizer started to drastically decrease its weight at hour 24, whereby the weight decreased approximately to 0.002 for every subsequent hour. Meanwhile, Fe fertilizer decreased drastically at hour 66, where the weight dropped from 0.10467 to 0.039. However, the final weights for both fertilizers at hour 72 were about the same. The highest chlorophyll contents for pak choi were recorded in the first treatment, which is 5 weeks in the pisciponic system. The first treatment of zinc and iron showed the highest chlorophyll contents. According to Babaeian et al. (2012), chlorophyll formation and photosynthesis need iron for the enzyme system and respiration of plants. In conclusion, this work has demonstrated the potential of this new slow-release zinc and iron fertilizer of palm stearin.